Physical quality of chicken patties containing red beans (Vigna angularis) with different filler levels of taro meal. Issue 1 (November 2021) - Nuhriawangsa, A M P; Hertanto, B S; Budiharjo, A; Swastike, W; Kartikasari, L R
Abstract: This research aims to evaluate the use of different filler levels of taro meal on the physical quality of chicken patties containing red beans ( Vigna angularis ). Patties produced from chicken meat with the ratio of red bean flour and taro flour as filler substitution for tapioca flour are 15:0 (CP0), 15:3 (CP1), 10:0 (CP2), 10:3 (CP3), 5:0 (CP4), and 5:3 (CP5). The analysis showed a significant difference in the tenderness (P<0.01), the value of pH, cooking loss, and water holding capacity (P<0.05) of patties. The addition of taro flour can increase the tenderness value of chicken patties. Reducing the amount of red beans resulted in a decrease in the pH value of chicken patties, but the increase in the use of taro meal did not result in a difference in the pH value. The highest cooking loss was achieved with the use of 5% red beans without taro meal. The highest water holding capacity of patties produced was obtained with a ratio of red bean and taro meal of 5:3. The conclusion is that adding 10% red beans and 3% taro flour red beans increased the physical quality of chicken patties and can be accepted by consumers.